APPLICABILITY OF ARTICLE 170-A OF THE NATIONAL TAX CODE TO UNDUE TAX PAYMENTS RESULTING FROM UNCONSTITUTIONAL NORMS (CIPEEX, 2025)
This article examines whether Article 170-A of Brazil’s National Tax Code applies to tax overpayments arising from unconstitutional norms, focusing on the prohibition of set-off prior to a final and unappealable judgment. It is a doctrinal legal study grounded in literature review and analysis of precedents from the superior courts. The objective is to determine whether the restriction in Article 170-A reaches taxes collected under a statute later held unconstitutional, in light of the principles of legal certainty, legality, and non-cumulativity. The method combines a systematic interpretation of the National Tax Code and the Federal Constitution with the provision’s teleology—preventing set-offs based on provisional judicial decisions and safeguarding the Treasury against shifts in case law. The results indicate that a rigid application of Article 170-A, including where unconstitutionality is recognized in concentrated constitutional review, may impair taxpayers’ right to a refund (repetição do indébito) and undermine the effectiveness of restitution; they also reveal persistent divergence in higher-court case law on whether res judicata is required to set off amounts unduly paid under a rule declared unconstitutional. The conclusion advocates a Constitution-consistent reading that reconciles the protective purpose of Article 170-A with taxpayers’ rights, through jurisprudential uniformization and a systematic approach that allows set-off without res judicata where unconstitutionality has been recognized with erga omnes and binding effects.
Keywords: refund of undue payment; unconstitutionality; Article 170-A of the National Tax Code; tax set-off